PENGARUH TAX AVOIDANCE, RETURN ON ASSET, CURRENT RATIO DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Angeline Paskaria Apriliani; Suryanto (E-Jurnal Akuntansi TSM, 2023)
This study aims to test what factors are like tax avoidance, return on asset, current ratio, debt to equity ratio, firm size, dividend payout ratio, and firm growth affect firm value in non financial firms listed on Indonesia Stock Exchange. Population of this study is non financial firms listed on Indonesia Stock Exchange since 2018 until 2021. This study used purposive sampling method with 93 company selected for a total 279 data over a three years period. The hypotheses in this research are tested using multiple regression method. The result of this study shows that return on asset also debt to equity ratio have a positife affect on firm value and firm growth has a negative affect on firm value. While, for other variables such as tax avoidance, current ratio, firm size, and dividend payout ratio do not affect firm value.